Syirkah Contract Scheme as an Alternative Property Financing in Collaboration between Islamic Banks and Developers - Beni Andriano; Tri Hidayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article discusses the application of shirkah contracts, particularly the Musyarakah Mutanaqisah (MMQ) scheme, in property financing by Islamic financial institutions. Shirkah contract is a form of business cooperation based on the principle of bearing risks and profits proportionally. MMQ is one of the relevant contemporary implementations of shirkah in the property sector, where the bank and the customer have joint ownership of the asset (house), and the customer gradually takes over the ownership. This research uses a descriptive qualitative method with a literature study approach from literature, fatwas, financial institution reports, and reliable media articles. The results show that although MMQ has been used by several Islamic banks in Indonesia, its application is still limited to bilateral relationships between banks and customers. Opportunities for strengthening shirkah contracts in the property sector can be done through strategic cooperation between Islamic banks and developers, which allows project financing from the early stages of development. The article also identifies challenges to MMQ implementation, such as low Islamic financial literacy, regulatory limitations, and financing risks. Therefore, synergy between financial authorities, the property industry, and the public is needed to optimize the role of MMQ in sharia-based property development.